The Threat of Technological Innovation, Job Insecurity, and Mediating Role of Digital Literacy, Personal Innovation, and Technological Innovation among University Students - Ratnawati, Shinta; Paska, Yesica Apriliana; Sadewo, Satrio Tegar; Ernawati, Nimas Jimi; Anggraeni, Dewi (Manunggal Halim Jaya, 2025)
Technological innovations, such as automation, robotics, and artificial intelligence, have significantly changed the world of work and posed new threats to job security. Students, as a group transitioning into the professional world, face high uncertainty due to these changes. This study aims to examine the relationship between the threat of technological innovation to student job insecurity by examining the mediating role of digital literacy, personal innovation, and technological innovation. This study uses a systematic literature review method based on the PRISMA 2020 guidelines to synthesize findings from relevant previous studies. Data sources were obtained from reputable international journals (Scopus, Web of Science, ScienceDirect) and SINTA-accredited national journals published between 2018 and 2025. The selection process included the identification, screening, eligibility, and inclusion of articles that met the criteria of focusing on the context of students or those transitioning to the world of work. The results of the study show that the threat of technological innovation is positively related to job insecurity, but this impact can be minimized through increased digital literacy and the development of personal and technological innovation among students. In addition, digital literacy has been proven to encourage innovation capabilities that strengthen resilience to technological disruption. The implications of this study encourage universities to integrate digital literacy curricula and innovation incubation programs as strategies to prepare graduates for the technology-based job market.